By the pen and what they write writing in Islamic art and culture - Blair, Sheila; Bloom, Jonathan (Jonathan M.) (Yale University Press, 2017)
Considered by Muslims as the only true art, calligraphy has played a prominent role in Islamic culture since the time of the prophet Muhammad. Exploring this central role of the written word in Islam and how writing practices have evolved and adapted in different historical contexts, this book provides an overview of the enormous impact that writing in Arabic script has had on the visual arts of the Islamic world. Approaching the topic from a number of different perspectives, the essays in this volume include discussions on the relationship between orality and the written word; the materiality of the written word, ranging from the type of paper on which books were written to monumental inscriptions in stone and brick; and the development of Arabic typography and the printed book. Generously illustrated, By Pen and What They Write is an engaging look at how writing has remained a foundational component of Islamic art throughout fourteen centuries